STUDY ON THE HOT CORROSION RESISTANCE OF AL0.75CRCOFENI HIGH ENTROPY ALLOY IN NA2SO4 AND V2O5 MOLTEN SALT MIXTURE WITH CYCLIC HEATING AT 1100Â°C - Muhammad Adriansyah, Ilham
High entropy alloys are a group of materials which contains five or more alloying elements with equiatomic or near-equiatomic ratios and some addition of minor elements. The composition of high entropy alloys affects their properties, making the materials potentially used at high temperatures. High temperature alloys are used for many applications, such as combustion chamber and nozzle for rockets. Rocket technology mastery is important for the sustainability of a country. However not many advanced countries are willing to share rocket technology. Therefore, the development of excellent materials for combustion chamber and nozzle for rockets is needed. In this study, the hot corrosion resistance of Al0,75CoCrFeNi high entropy alloy is tested to study the possibility of its use at high temperature containing sulfate salt at cyclic operating mode. A series of experiments were carried out to study the hot corrosion resistance of Al0,75CoCrFeNi high entropy alloy. The alloy was melted in a single DC electric arc furnace followed by homogenization at 1100°C for 10 hours. The cyclic hot corrosion tests were performed at 1100°C in molten salt mixture consisting of 50% weight Na2SO4 and 50% weight V2O5. One cycle represented exposure for 1 hour in the horizontal tube furnace and cooling for 15 minutes outside the furnace. The weight change of each sample was measured every cycle to obtain weight gain. The variation of cycles in this study were 5, 10, 15, and 25 cycles. The samples were then characterized using XRD, SEM-EDS, and optical microscope. Al0,75CoCrFeNi high entropy alloy had FCC and BCC microstructure in the as-cast state. However, after homogenization the BCC phase separates into A2 (disordered BCC) and B2 (ordered BCC) phases. During hot corrosion the BCC phase experienced depletion near the grain boundaries and on the surface of the alloy, due to Al2O3 formation consuming Al in the alloy. Hot corrosion kinetics occur in 3 stages, i.e., logarithmic kinetics at 1-5 cycle with a constant value of 0,953 mg.cm-2.hour-1, linear kinetics at 6-10 cycle with a constant value of -5,518 mg.cm-2.hour-1, and linear kinetics at 11-25 cycle with a constant value of -17,373mg.cm-2.hour-1. Hot corrosion started with Al2O3 formation on the outer layer, followed by Cr2O3 under it and a mix of alloying element oxides and spinel on the deepest part of the oxide layer. Next, molten salt penetrated the oxide layer by forming CrS and Fe2(SO4)3 due to acid fluxing. When the molten salt becomes basic, CrS transformed into Cr2O3 and reduced back to Cr by Al, forming Al2O3.